Genome sequence of Aedes aegypti, a major arbovirus vector. - Nene, V; Wortman, JR; Lawson, D; Haas, B; Kodira, C; Tu, Z; Loftus, B; Xi, Z; Megy, K; Grabherr, M; Ren, Q; Zdobnov, E; et al. (2007)
We present a draft sequence of the genome of Aedes aegypti, the primary vector for yellow fever and dengue fever, which at approximately 1376 million base pairs is about 5 times the size of the genome of the malaria vector Anopheles gambiae. Nearly 50% of the Ae. aegypti genome consists of transposable elements. These contribute to a factor of approximately 4 to 6 increase in average gene length and in sizes of intergenic regions relative to An. gambiae and Drosophila melanogaster. Nonetheless, chromosomal synteny is generally maintained among all three insects, although conservation of orthologous gene order is higher (by a factor of approximately 2) between the mosquito species than between either of them and the fruit fly. An increase in genes encoding odorant binding, cytochrome P450, and cuticle domains relative to An. gambiae suggests that members of these protein families underpin some of the biological differences between the two mosquito species.